Optical Coherence Tomography Angiography (OCT-A) in a Patient with Occult Retinal Dysfunction - Juliana Wons; Jana Dinges; Matthias D. Becker; Stephan Michels (Case Reports in Ophthalmological Medicine)
Multimodal imaging techniques were performed in a patient with a newly emerged visual field defect; a missing retinal lesion on fundus examination made the diagnosis challenging but infrared imaging showed a larger area of retinal abnormality temporal to the fovea. Indocyanine green angiography (IA) showed late hypofluorescence and there was mild hyperautofluorescence which is known from acute zonal occult outer retinopathy (AZOOR). Despite normal fluorescein angiography (FA) results, a perfusion loss in the outer retinal layer was detected by OCT-A. Similar OCT-A findings were recently described in patients with acute macular neuroretinopathy (AMN). Methods. The methods included FA and IA, spectral domain optical coherence tomography (SD-OCT), near infrared imaging, and autofluorescence imaging (AF), as well as OCT-A. Patient. A 36-year-old patient who suffered from acute symptoms of photopsia and scotoma on her left eye. She had an influenza-like illness two weeks earlier. The scotoma could be verified by visual field testing. Results. The affected retinal zone showed mild fading of external limiting membrane (ELM) and a disorganisation of the ellipsoid zone (EZ) on SD-OCT. OCT-A revealed a large area of reduced perfusion in the outer retinal vascular layer. Conclusion. OCT-A can help to detect reduced capillary network in patients with visual field defects and no visible fundus changes. This case seems to have features of different occult retinal disorders such as AZOOR and AMN.